Development And Quality Assessment Of Fermented Pegaga (Centella Asiatica) Tea - Chew , Shio Heong (2011)
Centella asiatica is a famous herb in Ayurvedic medicine and has a long history of being consumed around the world. The herb was reported to enrich with micro and macronutrients that contribute to it numerous phytochemical properties. In this study, C. asiatica undergone various stages of fermentation as follow: no fermentation (0 hr, CANF), partial fermentation (2 hrs, CAPF) and full fermentation (24 hrs, CAFF). The present study suggested that C. asiatica teas should be prepared at 100 °C for 10 min to obtain the maximum antioxidant capacity.